Occupational exposures to organic dust in Irish bakeries and a pizzeria restaurant - Viegas, Carla (2020)
For decades, occupational exposure to flour dust has been linked to a range of respiratory diseases, including occupational asthma, thought to result from exposure to fungi present in the flour. Antifungal resistance is of increasing prevalence in clinical settings, and the role of occupational and environmental exposures, particularly for specific fungal species, is of concern. Occupational exposure to flour dust can occur in a range of occupational settings, however, few studies have focused on restaurant workers. The objective of this study was to measure occupational exposure to flour and microbial contamination, including azole resistance screening, in two small commercial bakeries and in a pizzeria. Personal full shift inhalable dust measurements were collected from workers, and were analyzed for inhalable dust and fungi, bacteria, azole resistance, and mycotoxins. Samples of settled dust were collected, and electrostatic dust cloths (EDC) were deployed and analyzed for microbial contamination, including azole resistance screening, and mycotoxins. Geometric mean exposures of 6.5 mg m-3 were calculated for inhalable dust, however, exposures of up to 18.30 mg m-3 were measured—70% of personal exposure measurements exceeded the occupational exposure limit for flour dust of 1.0 mg m-3. The air and EDC fungal counts were similar to those reported in previous studies for similar occupational environments. The fungi were dominated by Penicillium genera, however Aspergillus genera, including Fumigati and Flavi sections, were observed using culture-based methods, and the Fumigati section was also observed by molecular tools. Both Aspergillus sections were identified on the azole resistance screening. Mycotoxins were also detected in the settled dust samples, dominated by deoxynivalenol (DON). The role of environmental exposure in both the development of antimicrobial resistance and the total mycotoxin body burden is a growing concern; therefore, the presence of azole-resistant fungi and mycotoxin contamination, although low in magnitude, is of concern and warrants further investigation.